Pengaruh Kualitas Pelayanan Bus Kota DAMRI Terhadap Kepuasan Pelanggan (Studi pada Penumpang Bus Kota DAMRI Bandung) - Fadhilah, Maulida Wahyu; Amalia, Sholihati (Jurnal Riset Bisnis dan Investasi, 2021)
Bandung is the 14th most congested cities in Asia according to the Asian Development Bank. Congestion that occurs is caused by the high use of private vehicles rather than the use of public transportation. One of the public transportations in Bandung is the DAMRI city bus. However, in the last three years there has been a decline in the number of DAMRI city bus passengers and various complaints have been found from the services provided. This study aims to determine the service quality and customer satisfaction of DAMRI Bandung city buses and the influence of DAMRI Bandung city bus service quality on customer satisfaction. This study uses a quantitative approach with a sample of 384 respondents. The results of this study indicate that service quality and customer satisfaction are in the good category. Then, service quality has a significant and positive effect on customer satisfaction with an effect of 65.8%.